The relationship between changes in health behaviour and initiation of lipid-lowering and antihypertensive medications in individuals at high risk of ischaemic heart disease - Hempler Nana; Krasnik Allan; Pisinger Charlotta; Jørgensen Torben (BMC, 2012)
Abstract Background It has been hypothesised that health conscious individuals tend to take better care of themselves by greater adherence to preventive medications. We examined, whether long-term changes in dietary habits and physical activity were associated with initiation of lipid-lowering and antihypertensive medications. Methods The study population consisted of two subsamples from the population-based cohort Inter99 study (1999-2006) in Copenhagen, Denmark: one with systolic blood pressure > 140 mmHg (N = 557) and one with total cholesterol > 7 mmol/L (N = 314). At a health examination, individuals completed a questionnaire about health behaviour and had their blood pressure and cholesterol measured at baseline and after five years. Data on medications were obtained through linkage to the Registry of Medical Product Statistics. Results Positive changes in physical activity (odds ratio =3.50; 95% CI 1.23-7.54) and in dietary habits (odds ratio = 2.08; 95% CI 1.03-4.21) were associated with an increased initiation of lipid-lowering medications. With respect to antihypertensives, no association was observed in terms of physical activity, but for diet, a positive trend in terms of initiation was observed among those with positive changes in dietary habits (odds ratio = 1.58; 95% CI 0.96-2.59). Conclusion Generally, we observed health conscious behaviour in terms of increased initiation of preventive medications among those who reported positive changes in health behaviour. This study therefore suggests that more attention should be given to identifying individuals and groups, who are less health conscious and thereby less likely to engage in either preventive medications or changes in health behaviours.